Testing the hybrid‐3‐D hillslope hydrological model in a controlled environment. Issue 2 (20th February 2016) - Hazenberg, P.; Broxton, P.; Gochis, D.; Niu, G.‐Y.; Pangle, L. A.; Pelletier, J. D.; Troch, P. A.; Zeng, X.
Abstract: Hillslopes are important for converting rainfall into runoff, influencing the terrestrial dynamics of the Earth's climate system. Recently, we developed a hybrid‐3‐D (h3D) hillslope hydrological model that gives similar results as a full 3‐D hydrological model but is up to 2–3 orders of magnitude faster computationally. Here h3D is assessed using a number of recharge‐drainage experiments within the Landscape Evolution Observatory (LEO) with accurate and high‐resolution (both temporally and spatially) observations of the inputs, outputs, and storage dynamics of several hillslopes. Such detailed measurements are generally not available for real‐world hillslopes. Results show that the h3D model captures the observed storage, base flow, and overland flow dynamics of both the larger LEO and the smaller miniLEO hillslopes very well. Sensitivity tests are also performed to understand h3Ds difficulty in representing the height of the saturated zone close to the seepage face of the miniLEO hillslope. Results reveal that a temporally constant parameters set is able to simulate the response of the miniLEO for each individual event. However, when one focuses on the saturated zone dynamics at 0.15 m from the seepage face, a stepwise evolution of the optimal model parameter for the saturated lateral conductivity parameter of the gravel layer occurs. This evolution might be related to the migration of soil particles within the hillslope. However, it is currently unclear whether and where this takes place (in the seepage face or within the parts of the loamy sand soil). Key Points: In this study, the h3D hillslope model is tested using Biosphere 2 LEO observations The h3D model captures observed hillslope flow and storage dynamics very well Results reveal the possibility of migrating soil particles close to the seepage face